Restorative Justice Approach in Dealing with Crimes at Police Level (A Study at Polresta and Polres Sorong) - Buinei, Gerson Sem; Hidaya, Wahab Aznul; Mursid, A. Faqih (Journal of Law Justice (JLJ), 2024)
In knowing and explaining the application of the Restorative Justice Approach in resolving criminal offences at the police level, it is essential to know and explain the influencing factors in overcoming criminal acts using this approach. Then the method used in this study is a sociological juridical approach. It identifies and conceptualizes law as a natural and functional social institution in a real-life system. Indonesian peoples have long practised the concept of a case settlement approach through restorative justice, such as in Papua, Bali, Toraja, Minangkabau, and other traditional communities that still hold their culture. In the event of a criminal offence by a person (including unlawful acts committed by children), the dispute is resolved internally in the customary community without involving state officials. The obligation to apply restorative justice approaches in the diversion process is not just a desirable approach but a requirement that has legal consequences if not complied with by law enforcement. It shows the importance of ensuring that efforts to resolve children's cases involve approaches that prioritize restorative justice to achieve more holistic justice and support the development of children in conflict with the law.